Regulação da biossíntese de exopolissacarídeos de Gluconacetobacter diazotrophicus por fosforilação de uma Tirosina quinase - Wanderley, Katyanne Maciel (2019)
Protein Phosphorylation by tyrosine kinases occurs in all living organisms and plays a central role in regulating a wide variety of cellular processes, such as proliferation and differentiation. Thus, a biological system in which protein phosphorylation by tyrosine protein is responsible for important role in exopolysaccharide (EPS) synthesis was explored in Gluconacetobacter diazotrophicus. The characteristics of the sequence encoding a protein tyrosine kinase in the genome of G. diazotrophicus Pal5 (GDI2549), kinase activity, evaluation of the influence of tyrosine kinase in G. diazotrophicus, and the effect on gene expression, when the bacterium was cultured in different carbon sources. The results indicate that GDI2549 is a tyrosine kinase that regulates the EPS biosynthesis in G. diazotrophicus, also suggesting that it presents kinase activity in different sources of carbon used during cultivation. In the mutant gumD strain of G. diazotrophicus, GDI2549 showed an autophosphorylation in radiolabeled cultures. The wild-type Pal5 strain of G. diazotrophicus showed different patterns of relative expression of the GDI2549 gene, when the bacterium was cultured on different carbon sources. This study demonstrated that EPS biosynthesis in G. diazotrophicus is regulated by a phosphorylation mechanism in positive feedback patterns, where the EPS presence is paramount in note.